Rangka kerja keselamatan transaksi bagi pelanggan pelayan berasaskan perdagangan elektronik - Abdullah, Abdul Hanan (Faculty of Computer Science and Information System, 2003)
Nowadays E-Commerce becomes more popular among online users for online trading. However, there are lots of intrusion issues on E-Commerce. Due to this main problem, this research project team A Secure Transaction Framework for Client-Server Based ECommerce have been doing research specialized in three main components which are, website and server security, authorised data security on client-server and secure data transfer on network layer. Research on website and server security currently have been developing Web Document Integrity Detector (WebDID) to overcome intrusion in website and web server. WebDID is an alternative method to protect web server by detecting unauthorised changes in web and sending an intrusion alarm directly to web server administrator. Hashing function implementation have been using in this system as its cryptography algorithm. In authorised data security on client and server research, researcher mainly focused on data intrusions that can occur anytime without users awareness. Researchers have been developing a system using intrusion detector approach base on differential analysis. This method enable to differentiate between intruders and normal activities by counting the amount of coming system calls on each activities. Research in secure data transfer on network layer has been discussed in detail on the importance to have secure Internet protocol in E-Commerce environment. This particular research successfully produced a protocol to suit AES encryption algorithm in Internet Protocol Security (IPSec).